Role of sea surface warming in convective activity over Europe and Northern Eurasia: estimates with sensitivity model experiments. (November 2019) - Yarinich, Yu I; Chernokulsky, A V; Semenov, V A; Latif, M
Abstract: The influence of sea surface warming on convective activity over Europe and Northern Eurasia is estimated from sensitivity model experiments by an atmospheric general circulation model, ECHAM5, with prescribed boundary conditions ("warm" and "cold" sea surface). Convective activity is analysed by using various indices (thermodynamic, dynamic, and composite). It is shown that warmer sea surface leads to a general increase in the thermodynamic indices that is broadly consistent with observations. Particularly, the observed increase in CAPE over the eastern part of the Mediterranean Sea, the Black Sea, and Eastern Europe is well reproduced in the sensitivity experiments. At the same time, the shear and helicity instability indices depend little on sea surface warming. The experiment with only Mediterranean and Black Seas warming tends to overestimate the increase in the thermodynamic indices near these seas and underestimate the increase in the other regions. There are several regions (the Iberian Peninsula, Mongolia, and Northern China) where the observations show a decrease in the convective indices. These negative changes are not reproduced in the model experiments, because their nature is, apparently, not related to sea surface warming.